Biotechnology in biopolymers developments applications & challenging areas - Tiwari, Atul; Srivastava, Ravi B. 1955- (Smithers Rapra, 2012)
This book provides up-to-date information on developments in the field of biopolymers. Each chapter details methods and techniques of synthesis and characterization, degradation of materials and industrial applications as well as current trends and future challenges. It will be useful for students and researchers working in biotech and polymer research.
Keywords: Biopolymers -- Biotechnology.; elektronické knihy; electronic books